Pengaruh Kualitas Pelayanan Jasa Verifikasi Impor terhadap Kepuasan Dan Loyalitas Pelanggan di PT Surveyor Indonesia (Persero) - Annisa, Aliftia Rizki (Universitas Brawijaya, Indonesia, 2014)
One effort to raise the rating of the company is to improve the quality of services that will impact the customer satisfaction and loyalty. Based on these problems, this study aims to analyze the impact of service quality on the Import Verification Services customer satisfaction and loyalty in PT Surveyor Indonesia (Persero). Subjects in this study are customers who have used services in the Import Verification PT Surveyor Indonesia (Persero) for at least 3 years using the test method used is an instrument that uses SPSS software 16.00 as for testing hypotheses using structural equation model (SEM) with software SmartPLS. Based on the analysis of SEM with PLS approach, it is known that the quality of services significantly influence customer satisfaction (t=14.1274). Then the quality of services significantly influence customer loyalty (t= 2.6584). Furthermore, a significant effect of customer satisfaction on customer loyalty (t=4.1955). It can be concluded that the quality of leadership services significantly influence customer satisfaction and loyalty.